Sex-specific phenotypical, functional and metabolic profiles of human term placenta macrophages - Daniel E. Paparini; Esteban Grasso; Franco Aguilera; M. Agustina Arslanian; Victoria Lella; Brenda Lara; Ana Schafir; Soledad Gori; Fátima Merech; Vanesa Hauk; Claudio Schuster; Marcelo Martí; et al. (Biology of Sex Differences)
Abstract Background Placental macrophages, Hofbauer cells (HBC) are the only fetal immune cell population within the stroma of healthy placenta along pregnancy. They are central players in maintaining immune tolerance during pregnancy. Immunometabolism emerged a few years ago as a new field that integrates cellular metabolism with immune responses, however, the immunometabolism of HBC has not been explored yet. Here we studied the sex-specific differences in the phenotypic, functional and immunometabolic profile of HBC. Methods HBC were isolated from human term placentas (N = 31, 16 from male and 15 female neonates). Ex vivo assays were carried out to assess active metabolic and endoplasmic reticulum stress pathways by flow cytometry, confocal microscopy, gene expression and in silico approaches. Results HBC from female placentas displayed a stronger M2 phenotype accompanied by high rates of efferocytosis majorly sustained on lipid metabolism. On the other hand, male HBC expressed a weaker M2 phenotype with higher glycolytic metabolism. LPS stimulation reinforced the glycolytic metabolism in male but not in female HBC. Physiological endoplasmic reticulum stress activates IRE-1 differently, since its pharmacological inhibition increased lipid mobilization, accumulation and efferocytosis only in female HBC. Moreover, differential sex-associated pathways accompanying the phenotypic and functional profiles of HBC appeared related to the placental villi environment. Conclusions These results support sex-associated effects on the immunometabolism of the HBC and adds another layer of complexity to the intricate maternal-fetal immune interaction. Graphical abstract